How Work Environment and Rewards Affects the Employee Engagement - Ria Marginingsih; Muhammad Khasan Khaeri (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: This study aimed to determine the effect of the work environment and reward on employee engagement at PT Futaba Industrial Indonesia. Design/methodology/approach: This study uses quantitative descriptive research methods. The results showed that the work environment influences employee engagement, wherein the T-statistics for the variable work environment (X1) on employee engagement variables (Y) amounted to 3,847 more than T-table 1,675. The original sample estimate value shows a positive value of 0.279, which indicates that the direction of the work environment variable (X1) to the employee engagement variable (Y) is a significant positive effect. Thus Ha was accepted into the study. Findings: The original sample estimate value shows a positive, indicating that the direction of the work environment variable (X1) to the employee engagement variable (Y) is a significant positive effect. The original sample estimate value shows that the relationship of the reward variable (X2) to the employee engagement variable (Y) is significantly positive. Research limitations/implications: This research is only used as a sample, and the population is only in the welding section because it is not allowed to conduct research, so the results of this study are not comprehensive for all units in the company. Future research is expected to research all units in the company so that the research results. Paper type: Research paper